The Factors That Influence Stress Among Students Participating in the Co-Curricular Activity at Universiti Tun Hussein Onn Malaysia (UTHM) - Nurul Asyiqin Mohd Kamal; Siti Norziah Ismail (Research in Management of Technology and Business, 2021)
The co-curricular activities are necessary for students in primary school, secondary school as well as college and university students. Next, co-curricular activity is programs and learning experiences that in some way complement what they are learning in school or university. The previous study stated it becomes difficult for students who are overly committed to various activities to remain engaged in their academic studies, complete their assignments within a reasonable amount of time, and feel stress-free. Therefore, this study attempts to know which factors that influence stress among students participating in co-curricular activities. The purpose of this research is to determine factors and to identify the relationship between factors and co-curricular activity that most influence stress among students participating in the co-curricular activity at Universiti Tun Hussein Onn Malaysia (UTHM). To achieve the purpose of this study, a quantitative method and descriptive analysis were used. A questionnaire was designed and was administered to a sample research that involved of 377 respondents from year 2 to year 4 students from all faculties in the Parit Raja campus at Universiti Tun Hussein Onn Malaysia (UTHM). Descriptive analysis are used, and discussion and conclusion made in the quantitative findings. Time management was the factors that most influence a student stress among three IVs. With the limitation to achieve a targeted number of respondents to answer this questionnaire, future researchers can carried out the research with longer time with a well-mannered way which it allow the research to increase the target respondents as more time are given to collect the data.